2021
DOI: 10.3389/fpubh.2021.726288
|View full text |Cite
|
Sign up to set email alerts
|

Waist-To-Height Ratio Is a More Accurate Tool for Predicting Hypertension Than Waist-To-Hip Circumference and BMI in Patients With Type 2 Diabetes: A Prospective Study

Abstract: Background: Anthropometric measures [i.e., body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR)] have been used as prediction factors for incident hypertension. However, whether any of these measures is superior to another in the matter of accuracy in predicting hypertension in diabetic patients has been controversial. The present prospective study aimed to determine whether WHtR is a more accurate tool for predicting hypertension than WHR and BMI in patients with type 2 diabetes.M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 46 publications
3
55
1
Order By: Relevance
“…Among the obesity-related indices included in this study, we found that WHtR had the highest AUC for the prediction of incident hypertension, followed by BRI and WHR in the male participants, compared to WHtR, LAP, and BRI in the female participants. In both sexes, WHtR had the strongest predictive ability for incident hypertension, which is consistent with previous studies [ 19 , 20 , 21 , 29 , 50 ]. In a prospective cohort study of Korean adults, the WHtR cutoff value for predicting DM, cardiovascular disease, hypertension, and metabolic syndrome was 0.5 [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among the obesity-related indices included in this study, we found that WHtR had the highest AUC for the prediction of incident hypertension, followed by BRI and WHR in the male participants, compared to WHtR, LAP, and BRI in the female participants. In both sexes, WHtR had the strongest predictive ability for incident hypertension, which is consistent with previous studies [ 19 , 20 , 21 , 29 , 50 ]. In a prospective cohort study of Korean adults, the WHtR cutoff value for predicting DM, cardiovascular disease, hypertension, and metabolic syndrome was 0.5 [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…BRI is developed to advance WC, which combines height, and WC and captures the body shape as an ellipse or an oval to predict %BF and total % visceral adipose tissue [ 15 ]. WHtR was also reported as one of the useful anthropometric indexes in screening cardiovascular diseases by deeming the simultaneous impact of height and WC on body fat composition [ 29 ]. Our findings are consistent with previous studies, which revealed the high discriminatory power of BRI and WHtR (WHtR cut-off values of approximately 0.5 in both genders) in detecting MetS [ 18 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis using logistic regression showed that WHtR had the highest odds ratio in the prediction of peripheral neuropathy compared to WC and BMI. Though, some studies have reported the significant abilities of obesity indices to predict cardiovascular diseases ( 1 , 2 , 5 ), with some reports demonstrating that WHtR had higher predictive power than WC and BMI ( 3 , 4 ), very few studies have ventured into the predictive abilities of these obesity indices for peripheral neuropathy ( 8 , 9 ). However, Bulum et al ( 11 ) reported that WHtR was more accurate than WC in predicting diabetic nephropathy, which is also a microvascular complication of DM.…”
Section: Discussionmentioning
confidence: 99%
“…It is the ratio of waist circumference (WC) as the numerator and height as the denominator, all in the same units. Generally, it has been reported that WHtR is a more accurate measure of metabolically significant obesity than body mass index (BMI), WC, and waisthip ratio (WHR) (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%